The Influence of Capital Structure and Business Risk on Company Value with Company Size as a Moderating Variable - Tika Febryana; Muanifah , Suciati (Universitas Pamulang, 2024)
This research aims to determine the influence of Capital Structure and Business Risk on Company Value with Company Size as a moderating variable in agricultural sector companies listed on the Indonesia Stock Exchange in 2018-2022. The type of research used in this research is descriptive research with a quantitative approach. The data source used is secondary data with a data collection method, namely documentation. Research was conducted on 9 agricultural sector companies listed on the Indonesia Stock Exchange in 2018-2022. The analytical tool used in this research is analysis with the help of the E-Views version 12 program. Based on the test results using the f test, it shows a result of 0.008982, proving that Capital Structure and Business Risk have a simultaneous effect on Company Value. This research also uses a t test showing a result of 0.0057 proving that Capital Structure has an effect on Company Value, and showing a result of 0.1543 proving that Business Risk has no effect on Company Value. This research also shows a result of 0.9312 that company size is unable to moderate the influence of capital structure on company value. And with a result of 0.2389, company size is unable to moderate the influence of business risk on company value.